The Wisdom of Kinayah in Qur'anic Sexual Terminology: A Linguistic Analysis of Meaning, Ethics, and Aesthetic Expression in Divine Discourse - A. Rahmat Hidayat; Muhammad Yusuf; Andi Miswar (Sunan Kalijaga International Journal on Islamic Educational Research, 2024)
Sex in the Qur'an is mentioned with several variations of terms, namely mass, afda, ata, asyiru, basyiru and rafats. The six terms are kinayah which have high aesthetic value. This study will describe the wisdom of using these terms by focusing on looking at the aspects of the kinayah contained. To obtain this, the author uses the thematic interpretation method with a linguistic approach, especially balagah. The results of the study show that sex in the Qur'an is considered something sacred and has the function of continuing the lineage. Terms such as mass, afda, ata, asyiru, basyiru and rafats in the verses about sex as kinayah have their own emphases. The emphasis can be detected in the basic meaning of each term. The wisdom of using these terms includes proof of the greatness of the language of the Qur'an, affirmation of manners in conveying meaning and affirmation of sex as a form of outpouring of love and affection. This research has implications for the scientific field, especially in the fields of interpretation and literature.